2020
DOI: 10.1016/j.pt.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Preclinical Imaging of Hepatosplenic Schistosomiasis

Abstract: Schistosomiasis, a neglected tropical disease, is a major cause of chronic morbidity and disability, and premature death. The hepatosplenic form of schistosomiasis is characterized by hepatosplenomegaly, liver fibrosis, portal hypertension and oesophageal varices, whose rupture may cause bleeding and death. We review currently available abdominal imaging modalities and describe their basic principles, strengths, weaknesses, and usefulness in the assessment of hepatosplenic schistosomiasis. Advanced imaging met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 99 publications
(98 reference statements)
0
27
0
Order By: Relevance
“…Additionally, treated SchPAH patients have better survival rates compared to untreated SchPAH patients (89% and 69%, respectively, at 60 months) ( 74 ). A recent systematic review of the literature confirmed the better prognosis of SchPAH in relation to IPAH ( 11 ); however, similarly to the hemodynamic findings of this systematic review, the inclusion of several studies from just one center (potential sample overlap) might have influenced the systematic review findings. Additionally, this interpretation is confounded by the lack of effective non-invasive screening methods to uniformly diagnose PAH early in its course.…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 50%
See 1 more Smart Citation
“…Additionally, treated SchPAH patients have better survival rates compared to untreated SchPAH patients (89% and 69%, respectively, at 60 months) ( 74 ). A recent systematic review of the literature confirmed the better prognosis of SchPAH in relation to IPAH ( 11 ); however, similarly to the hemodynamic findings of this systematic review, the inclusion of several studies from just one center (potential sample overlap) might have influenced the systematic review findings. Additionally, this interpretation is confounded by the lack of effective non-invasive screening methods to uniformly diagnose PAH early in its course.…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 50%
“…Hepatosplenic schistosomiasis (HSS) is characterized by hepatosplenomegaly, liver fibrosis, portal hypertension, and esophageal varices ( 11 ), and is generally thought to be a necessary precursor state on the path to development of pulmonary hypertension (PH) ( 12 ). The chronic form of hepatosplenic schistosomiasis follows a host immune system response to eggs generated by the paired flukes and deposited into the mesenteric and portal venous system.…”
Section: Introductionmentioning
confidence: 99%
“…This denoted greater amelioration of schistosomiasis-induced pathology which results from immune-mediated granulomatous responses against Schistosoma eggs trapped in tissues. These are likely to cause serious local and systemic pathological effects associated with granuloma formation and fibrosis [53]. The significant reduction in hepatic granuloma size could be attributed to the distribution of PZQ [13,54] and MFS [55,56] to the liver of mice.…”
Section: Discussionmentioning
confidence: 99%
“…This denoted greater amelioration of schistosomiasis-induced pathology which results from immune-mediated granulomatous responses against Schistosoma eggs trapped in tissues. These are likely to cause serious local and systemic pathological effects associated with granuloma formation and brosis [53]. The signi cant reduction in hepatic granuloma size could be attributed to the distribution of PZQ [13,54] and MFS [55,56] to the liver of mice.…”
Section: Discussionmentioning
confidence: 99%